Pendekatan Scientific Dapat Meningkatkan Aktivitas Dan Hasil Belajar Siswa Pada Mata Pelajaran IPA di Kelas VA SD INPRES Kotapulu - Moh. Nasihin; Mohammad Jamhari; Samsurizal M. Suleman (Mitra Sains, 2016)
The aim of this reserach is to describe the increasing of the activities and the learning outcomes of student on IPA subject by using the scientific approach in class VA SD Inpres Kotapulu. The learning was focused on the weathering topic in the first cycle while in the second cycle was the identifying the types of soil topic. The method used in this study is a classroom action research (PTK). The instrument data collection used are the initial test sheets, the observation activity sheets for teacher and student, and the final test sheets. The results showed that there is an increasing in the activities of teacher and students also the learning outcomes of student from the first cycle until the second cycle. The increasing of the student’s learning outcomes is proved by the result the attainment of absorption average score and the percentage of classical completeness that increase from the pra-action, the first cycle and the second cycle respectively. Based on these findings, it can be concluded that the learning of subject IPA by using the scientific approach can increase the activities and the student learning outcomes of student in class VA SD Inpres Kotapulu.